2020
DOI: 10.1039/c9cp04775a
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of a multifunctional di-triazole derivative with Alzheimer's Aβ42monomer and Aβ42protofibril: a systematic molecular dynamics study

Abstract: The molecular dynamics simulations results highlighted that the multi-target-directed ligand 6n stabilizes the native α-helix conformation of the Aβ42 monomer and induces a sizable destabilization in the Aβ42 protofibril structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 105 publications
0
14
0
Order By: Relevance
“…62,63 Our previous REMD simulations showed that norepinephrine can inhibit Aβ dimerization by binding to central (16KLVFFA21) and C-terminal (31IIGLMV36) hydrophobic sites. 64 Increasing number of MD simulation studies revealed that small molecules (including morin, 65 NQTrp, 66 12-crown-4 ether, 67 EGCG, 68 wgx-50, 69 dihydrochalcone, 70 a resveratrol and clioquinol hybrid compound, 71 caffeine and ditriazole derivative 72,73 ) preferentially bind to the hydrophobic cavity of U-shaped Aβ protofibrils/fibrils and destroy their structures. Recently, we have explored the disruptive mechanism of recently resolved LS-shaped Aβ 42 protofibril by EGCG 57 and catechin 74 and found that those In spite of extensive experimental and computational studies, the atomic mechanism of dopamine in disaggregating preformed Aβ fibrils and inhibiting Aβ aggregation remains largely unclear.…”
Section: ■ Introductionmentioning
confidence: 99%
“…62,63 Our previous REMD simulations showed that norepinephrine can inhibit Aβ dimerization by binding to central (16KLVFFA21) and C-terminal (31IIGLMV36) hydrophobic sites. 64 Increasing number of MD simulation studies revealed that small molecules (including morin, 65 NQTrp, 66 12-crown-4 ether, 67 EGCG, 68 wgx-50, 69 dihydrochalcone, 70 a resveratrol and clioquinol hybrid compound, 71 caffeine and ditriazole derivative 72,73 ) preferentially bind to the hydrophobic cavity of U-shaped Aβ protofibrils/fibrils and destroy their structures. Recently, we have explored the disruptive mechanism of recently resolved LS-shaped Aβ 42 protofibril by EGCG 57 and catechin 74 and found that those In spite of extensive experimental and computational studies, the atomic mechanism of dopamine in disaggregating preformed Aβ fibrils and inhibiting Aβ aggregation remains largely unclear.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Until now, an effective treatment for AD does not yet exist. It is crucial to find effective inhibitors for the treatment of AD. A large number of experimental studies reported that several different types of potential inhibitors, including nanoparticles, , short peptides, small molecules, , multitarget-directed ligands, and antibodies, , are able to dissociate Aβ fibrils and/or inhibit Aβ aggregation. Inspired by those experimental studies, several computational groups investigated the inhibitory mechanisms using MD simulations.…”
Section: Introductionmentioning
confidence: 99%
“…However, in our opinion CHC will remain as the most probable target of BSBs and within it both phenylalanines 19 and 20 are supposedly crucial for the action of inhibitor molecules. This notion is also substantiated by the results obtained by use of different fibril models and small non‐peptide molecule inhibitors 52‐56 …”
Section: Discussionmentioning
confidence: 62%